Endodontic Treatment of a Mandibular Second Premolar with Three Roots and Three Canals - Bonny Paul; Kavita Dube (Case Reports in Dentistry)
Complex root canal system with atypical variations is a common finding among mandibular premolars. Endodontic treatment in these teeth may not be successful due to the failure to recognise and treat multiple canals. This paper presents endodontic treatment of a mandibular second premolar with three roots and three canals.